Interim analysis of START: Study in asia of the combination of TACE (transcatheter arterial chemoembolization) with sorafenib in patients with hepatocellular carcinoma trial - Young‐Hwa Chung; Guohong Han; Jung‐Hwan Yoon; Jijin Yang; Jianhua Wang; Guo‐Liang Shao; Byung Ik Kim; Teng‐Yu Lee; Yee Chao (2012)
Transarterial chemoembolization (TACE) represents a first-line noncurative therapy for hepatocellular carcinoma (HCC). Sorafenib, a multikinase inhibitor, has been shown to be effective and safe monotherapy in patients with advanced HCC and the current study reports the interim results of a prospective Phase II, open label, trial investigating the safety and efficacy of the combination of sorafenib and conventional TACE in patients from the Asia-Pacific region with intermediate HCC. Patients with histologically or clinically diagnosed HCC were treated with conventional TACE followed by sorafenib 4 to 7 days later. TACE was performed by selective transarterial chemotherapy in the vessels feeding the tumor with an emulsion of lipiodol (5-20 ml) and doxorubicin (30-60 mg) followed by embolization with absorbable particles (gel foam). TACE/sorafenib cycles were repeated every 6-8 weeks. Primary objectives were to evaluate the safety and tolerability, in addition to the efficacy of TACE combined with sorafenib for HCC. A total of 147 patients were included in the intention-to-treat analysis and received at least one dose of sorafenib. Gastrointestinal AEs were reported by 62.6% of patients while 57.8% reported skin AEs although most were mild to moderate. The mean number of cycles undertaken was 2.1 and 63.3% of patients achieved either partial response or stable disease. Clinically, the disease control rate was 91.2% while the overall response rate was calculated as 52.4%. Our study shows that concurrent sorafenib and TACE therapy is safe and effective with no unexpected side effects.